EFEKTIVITAS KOMUNIKASI NONVERBAL DALAM PENGEMBANGAN BISNIS GLOBAL: TANTANGAN DAN PELUANG DI ERA GLOBALISASI - Tiwow, Clara; Biasane, Achmad Nasir; Paramita, Gemala; Syahiruddin, Syahiruddin (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
This research explores the role of nonverbal communication in the context of global business in the era of globalization. The main problem is cultural differences that affect cross-cultural communication, especially in terms of intimacy and individuality. The purpose of the study is to evaluate the balance between intimacy and recognition of cultural differences, identify cross-cultural communication challenges due to globalization and technology, and assess the impact of education and political participation in Indonesia on global communication. The method used is a literature review with a qualitative approach, collecting data from academic sources to analyze the findings. The results show that the balance between intimacy and individuality is crucial for effective communication, the development of cross-cultural communication competencies is important to address the challenges of globalization and technology, and improvements in education and political participation can im